Geochemical and petrographic characteristics of sediments along the transboundary (Kenya–Tanzania) Umba River as indicators of provenance and weathering - Kimeli Amon (De Gruyter, 2021)
The Umba River basin is one of the smaller-scale hydrological basins in the East African region. It traverses two countries, with its catchment in the Usambara mountains in Tanzania, while it drains its waters to the Indian Ocean in Vanga, Kenya. The chemical and mineralogical compositions of the riverbank and bottom sediments of the Umba River were analyzed and evaluated to describe their source characteristics and provenance. The dominant minerals include quartz, K-feldspars, plagioclase, hornblende, pyroxenes, muscovite, biotite, and likely presence of clays such as kaolinite. The chemical index of alteration of the sediments indicate a moderate to high degree of alteration. They reflect a dominant mafic to intermediate igneous provenance consistent with the geology of the Umba River catchment that is characterized by the outcrops of the granitic Precambrian basement and the quartz-dominated Paleozoic Karoo Supergroup, overlain by Mesozoic and Cenozoic sediments dominated by both mafic and felsic minerals. The similarity of the chemical and mineralogical compositions of the Umba River sediments from source to mouth further indicates a uniform source in the upper course of the river and only subordinate contributions from the lower course where it passes the Karoo and the younger sediments.